Discursive strategies of Turkey's AK Party : a critical analysis (2002-2015) - Syaza Farhana binti Mohamad Shukri (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
The Adalet ve Kalkınma Partisi (AKP) in Turkey, or better known as the Justice and Development Party, has been accused of Islamising society through its conservative policies that overlap with discourses originating from the Islamic faith. At the same time, the AKP government has maintained that it abides by Turkish secularism. By using discursive analysis as its theoretical framework, this research identifies and analyses the extent to which the AKP's discursive strategy has changed over the years to discover whether the party truly has a hidden agenda or if the shifts serve as strategies to win votes. For this research, the thesis uses both qualitative and quantitative methods. By gathering data from primary sources such as official documents and newspaper articles, a document analysis was done to gather the frequency of specific terms appearing in these documents. Furthermore, secondary sources from articles were collected and analysed using process tracing to find out the reasons for the rising religious discourse. Finally, statistical analysis was done by applying the Pearson Correlation to test the relationship between religious discourse and political dominance. The thesis highlights how while the party has actively rearticulated religious discourse since 2002, there is a shift in religious discourse in which it has become more specific with imminent policy ramifications. The changes observed are related to the perceived threats faced by the party, with Islamic discourse rising and depleting with the amount of challenges it faces by other institutions within Turkey. As a result, the AKP cannot be said to be a party that had always intended to turn Turkey into a religious country. The strategies undertaken by the party in the last 13 years (2002-2015) showed that the shifts in discourse were to manage the support it received by conservative Turks, rather than as an upfront to the secular establishment.